(untitled) (REMUNOM, 2024)
Cardiovascular disease is one of the leading causes of death in Brazil and worldwide. There are several factors responsible for the development of cardiovascular risk among them: inadequate diets, smoking, sedentary lifestyle, adiposity, overweight and alcohol consumption. The aim of this study was to investigate cardiovascular risk in patients assisted in a nutrition school clinic. The work was developed based on a retrospective cross-sectional research, constituting a quantitative, descriptive study with documentary research. In the analysis of anthropometric indicators, pre-obesity (37.1%) was observed in the individuals investigated, for waist circumference 58.1% presented risks, following the waist-height ratio 54.5%. The results of this study demonstrated risk for cardiovascular diseases in patients assisted in the nutrition school clinic, thus, the present study is of great importance, because from the identification of cardiovascular risk it is possible to prevent and reduce the risk of morbidity and mortality for such diseases, in addition to enabling the nutrition professional through educational intervention to improve the modifying factors of cardiovascular risk.